Historical Demography and Species Distribution Models Shed Light on Speciation in Primates of Northeast India - Mihir Trivedi; Kunal Arekar; Shivakumara Manu; Lukas F. K. Kuderna; Jeffrey Rogers; Kyle Kai‐How Farh; Tomas Marques Bonet; Govindhaswamy Umapathy (Ecology and Evolution, 2025)
ABSTRACT Past climate change is one of the important factors influencing primate speciation. Populations of various species could have risen or declined in response to these climatic fluctuations. Northeast India harbors a rich diversity of primates, where such fluctuations can be implicated. Recent advances in climate modeling as well as genomic data analysis has paved the way for understanding how species accumulate at a particular geographic region. We utilized these methods to explore the primate diversity in this unique region in relation to past climate change. To ascertain the population level changes, we inferred the demographic history of nine species of primates found in Northeast India and compared it with species distribution models of Pliocene and Pleistocene period. Through this study, we are able to provide a detailed picture of how past climatic changes have resulted in the present species diversity and this mixture of species have either originated in the region or have dispersed from mainland Southeast Asia. We observe that effective population size has decreased for all the species, but distributions are different for all the four genera: Macaca, Trachypithecus, Hoolock and Nycticebus. It also gives an idea about how each species is affected differently by climate change, and why it should be given emphasis in framing species‐wise conservation models for future climate change.